WHAT UNITS SHOULD WE EMPLOY? “TWO DISCIPLINES” IN PERSONALITY PSYCHOLOGY - Romero, Estrella (Anales de Psicología / Annals of Psychology, 2005)
One of the more pervasive controversies in personality psychology deals with the units needed to define the discipline. The problem was posed by G.W. Allport some decades ago; then, it was widely discussed during the consistency crisis, and now, it seems to arise again, with two confronted proposals: trait models (particularly, the Five Factor Model) and socicognitive models. This paper reviews the debate, examining both positions, their history, statements and critical points. The paper also discusses to what extent the two proposals are actually antagonistic, and reviews the integrative options. This critical review concludes that, in spite of the differences, trait-based and sociocognitive models show nontrivial similarities, which open doors to integration. Personality psychology should look at a wide variety of units (from the most static to the most mutable), and, for that reason, multilevel models are shown as an interesting option.